Relation of rice intake and biomarkers of cadmium for general population in Korea - Kim, Soo-Hwaun; Lim, Young-Wook; Park, Kyung-su; Yang, Ji-Yeon (ELSEVIER GMBH, 2017)
Environmental exposure to cadmium can cause renal damage. Foods containing cadmium are generally regarded as the main environmental sources of human exposure to cadmium. In this study, foods that are ingested in large amounts, including rice and other types of food with a high concentration of cadmium, were investigated to determine the correlation between the foods' cadmium content and biomarkers. The datasets required for this study, including blood cadmium concentration, biomarker concentration, and data on the amount of consumption by food item, were obtained from KNHNES. Furthermore, data on food groups with high daily exposure to hazardous amounts of cadmium were obtained by monitoring raw food sources from 2010 to 2012. The investigation was then followed by correlation analysis, which was performed to assess the relationship between the amount of rice consumption and cadmium concentration. The Pearson coefficient analysis on the relationship between the amount of food consumption and the biomarker showed that the correlation between foods' cadmium content and blood cadmium and that of between foods' cadmium content and other biomarkers were confirmed as statistically significant in the case of the cadmium content of white rice, while, in the case of brown rice, it was confirmed by a few biomarkers.